1998
DOI: 10.1007/s004170050100
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for balance between lower normal pressure control and hypotony in mitomycin trabeculectomy

Abstract: IOP of 8 mm Hg 9-14 days after surgery may be advisable in patients with preoperative multiple medications in whom IOP control to lower normal level is attempted with mitomycin C trabeculectomy. Knowledge of this may be helpful in deciding when laser lysis of sutures is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(49 reference statements)
1
19
0
1
Order By: Relevance
“…15 A balance must be sought between the risks of inducing hypotony and ensuing complications and the attainment of a safe IOP facilitating long-term successful surgery. 10 Analysis of factors contributing to postoperative complication is limited in this study because of a relatively low incidence. It is also important to emphasize that this study did not assess bleb morphology in the early postoperative period.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…15 A balance must be sought between the risks of inducing hypotony and ensuing complications and the attainment of a safe IOP facilitating long-term successful surgery. 10 Analysis of factors contributing to postoperative complication is limited in this study because of a relatively low incidence. It is also important to emphasize that this study did not assess bleb morphology in the early postoperative period.…”
Section: Resultsmentioning
confidence: 97%
“…[10][11][12]14,16 A retrospective analyses of 92 glaucoma patients with antimetabolite-augmented filtering surgery suggested that 16 mm Hg on day 1 predicted long-term success (r21 mm Hg without medication) and failure with an accuracy of 88.8 and 55.5%, respectively. 12 Another retrospective assessment involved a 2-year follow-up on 203 eyes undergoing unaugmented trabeculectomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 This is especially beneficial in Mitomycin C enhanced trabeculectomy where low IOP in the first two postoperative weeks is a risk factor for more prolonged hypotony. 18 Trabeculectomy using a small scleral flap appears to provide medium to long-term IOP control comparable to large flap techniques 12,15,19 and may offer potential advantages: reduced surgical tissue trauma, a larger area of undisturbed sclera and conjunctiva should repeat surgery be required, and reduced astigmatism induction. 20 Potential disadvantages include possible decreased control over aqueous flow, technical challenges including difficulty in dissecting a large treatment area for antimetabolite application and difficulty in controlling subconjunctival bleeding if the conjunctival incision is small.…”
Section: Introductionmentioning
confidence: 99%
“…We considered therefore that a cutoff IOP was more suitable for evaluating postoperative IOP after trabeculectomy. In addition, we considered the relationship between long-term IOP reduction and the cutoff IOP with reference to a study by Hara et al 21 Most surgical treatments for glaucoma, including MMC trabeculectomy, bypass the canal of Schlemm and drain aqueous humor into the subconjunctival space. 21 Long-term scarring of the conjunctiva and scleral flap reduces the effectiveness of these procedures over time and results in increasing IOP.…”
Section: Discussionmentioning
confidence: 99%